2015
DOI: 10.1007/s11356-015-4776-0
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of water reservoirs affected by acid mine drainage: geochemical, mineralogical, and biological (diatoms) properties of the water

Abstract: This work presents a combination of geochemical, mineralogical, and biological data obtained in water reservoirs located in one of the most paradigmatic mining regions, suffering from acid mine drainage (AMD) problems: the Iberian Pyrite Belt (IPB). Four water reservoirs located in the Spanish sector of the IBP, storing water for different purposes, were selected to achieve an environmental classification based on the effects of AMD: two mining dams (Gossan and Águas Ácidas), a reservoir for industrial use (Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…In the present study, we assessed the relative contribution of neutral and deterministic processes in the recovery of the yellow perch (Perca flavescens) microbiome assembly following an experimental metallic exposure gradient. Polymetallic contamination in aquatic ecosystems mostly results from exposure to acid mine drainages (AMD) occurring around the world [24][25][26][27][28][29][30][31][32][33][34]. For instance, in the natural Canadian lakes, the cadmium (Cd) concentration reaches 9 ppb (parts per billion) in perch liver/water [35,36], and it has a clear quantitative impact on the perch physiology, gene expression, and genotype diversity [37].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we assessed the relative contribution of neutral and deterministic processes in the recovery of the yellow perch (Perca flavescens) microbiome assembly following an experimental metallic exposure gradient. Polymetallic contamination in aquatic ecosystems mostly results from exposure to acid mine drainages (AMD) occurring around the world [24][25][26][27][28][29][30][31][32][33][34]. For instance, in the natural Canadian lakes, the cadmium (Cd) concentration reaches 9 ppb (parts per billion) in perch liver/water [35,36], and it has a clear quantitative impact on the perch physiology, gene expression, and genotype diversity [37].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, from an ecological point of view, AMD defines extreme environments (very low pH values, high metal solubility and the presence of iron colloids) (e.g., [10,11,12]) with a deficiency in carbon and inorganic phosphorus, that are crucial to the efficient functioning of biological communities. Lack of these nutrients increase the impact of stress on organisms, and thus (1) impacted communities experience high metal concentrations and very low pH, which lead to a decrease in the diversity of algal species (i.e., [13,14,15,16]) and (2) communities are limited to tolerant organisms that are capable of surviving in these extreme conditions, and are characterized by a simple ecosystem dominated by acidophilic and acid-tolerant organisms [10,17,18,19,20]. These organisms act as important players, ensuring primary production and interfering in the mobility of dissolved chemical species in the aquatic environment [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…In other cases, the weathering of minerals in the material being exploited can have stronger effects, such as AMD. Valente et al (2016) and García-Lorenzo et al (2016) describe the effects of AMD in two decommissioned mining districts, the Iberian pyrite belt in SW Spain and SE Portugal and the La Unión district in Murcia (SE Spain). Valente et al (2016) describe the geochemical and mineralogical characteristics of water in four artificial reservoirs in the Iberian pyrite belt that have been affected by AMD.…”
Section: Mining and Pollution: Effects On Water And Aquatic Systemsmentioning
confidence: 99%
“…Valente et al (2016) and García-Lorenzo et al (2016) describe the effects of AMD in two decommissioned mining districts, the Iberian pyrite belt in SW Spain and SE Portugal and the La Unión district in Murcia (SE Spain). Valente et al (2016) describe the geochemical and mineralogical characteristics of water in four artificial reservoirs in the Iberian pyrite belt that have been affected by AMD. They found that the reservoirs had been affected by AMD to different degrees, and that this was reflected in the characteristics of the biota present, particularly in the compositions of epipsammic diatom communities.…”
Section: Mining and Pollution: Effects On Water And Aquatic Systemsmentioning
confidence: 99%